Bridging Financial Knowledge and Investment Decisions: Evidence from Students of the Faculty of Islamic Economics and Business, IAIN Ponorogo - Rahmawati, Yunaita; Ahmad, Raisha Salisa (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: Although awareness of financial literacy is increasing, participation in Indonesia’s capital market remains low, with only about 0.4% of the population actively investing. Therefore, this study aims to examine the factors influencing investment interest among students of the Faculty of Islamic Economics and Business (FEBI) at IAIN Ponorogo. Research Methods: A quantitative method was employed using questionnaires distributed to 212 fifth-semester students during the 2018/2019 academic year. Multiple linear regression was applied to examine the effects of investment knowledge and minimum investment policies on investment interest. Results: The findings reveal that investment knowledge has a positive and significant effect on students’ investment interest, while minimum investment policies show no significant effect. However, both variables jointly have a significant influence. Conclusion: The results highlight the need for capital market authorities and educational institutions to enhance financial literacy and encourage active student participation in investment activities.